A case report of HER2-positive descending colon cancer with peritoneal metastasis and literature review - Lv, Yaochun; Qian, Zhengpeng; Wu, Dewang; Zhu, Chengzhang; Zhang, Jipeng; Ning, Yeping; Du, Binbin (Frontiers in Oncology, 2025)
Human epidermal growth factor receptor 2 (HER2) is an anti-cancer drug target for colon cancer. Among patients with colorectal malignancy (colorectal cancer, CRC), those with HER2 mutations have a poor overall prognosis and a significantly increased drug resistance. In recent years, anti-HER2 therapeutic drugs have developed rapidly. According to several clinical studies and case reports, anti-HER2 therapy, as an emerging anti-cancer approach, plays a crucial role in the treatment of HER2-positive CRC patients. Here, we present a case of HER2-positive descending colon cancer with peritoneal metastasis. The patient is a 26-year-old male, diagnosed with malignant tumor of the descending colon with peritoneal metastasis in April 2020. After multiple treatment modalities, the disease progressed. After chemotherapy with Trastuzumab Deruxtecan (T-DXd/DS-8201), the metastatic foci significantly shrank, and after surgical resection, a tumor-free state (NED) was achieved. Up to now, the patient’s survival period has reached 56 months.